2021
DOI: 10.3390/ijms222212452
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Use: Device Market, Study Design, and Emerging Evidence of Biological Consequences

Abstract: Electronic cigarettes are frequently viewed as a safer alternative to conventional cigarettes; however, evidence to support this perspective has not materialized. Indeed, the current literature reports that electronic cigarette use is associated with both acute lung injury and subclinical dysfunction to the lung and vasculature that may result in pathology following chronic use. E-cigarettes can alter vascular dynamics, polarize innate immune populations towards a proinflammatory state, compromise barrier func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…Concerning the findings of other studies investigating the physiological effects of using coolant containing e-liquids, using human bronchial epithelial cell cultures, previously, another study found that treatment with menthol significantly increased mitochondrial ROS via the TRPM8 receptor [30] . BEAS-2B cell exposures reported by these investigators consisted of aerosol treatments, in which cells were exposed for two separate 1.5-minute durations, separated by an incubation period; however, our cell treatment protocol conducted cell culture exposures through direct stimulation (e-liquid being directly pipetted into cell-culture media) as reported recently [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the findings of other studies investigating the physiological effects of using coolant containing e-liquids, using human bronchial epithelial cell cultures, previously, another study found that treatment with menthol significantly increased mitochondrial ROS via the TRPM8 receptor [30] . BEAS-2B cell exposures reported by these investigators consisted of aerosol treatments, in which cells were exposed for two separate 1.5-minute durations, separated by an incubation period; however, our cell treatment protocol conducted cell culture exposures through direct stimulation (e-liquid being directly pipetted into cell-culture media) as reported recently [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
“…However, n contrast to Omaiye et al [33] , which assessed the cytotoxicity induced by different treatments, our study assessed differences in ROS production. Additionally Omaiye et al [33] used aerosol exposures, whereas our study conducted cell-culture exposures via direct stimulation [32] . We further determined the cytotoxicity of the cooling agents, when WS-23 was treated to BEAS2B cells for hazard characterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitation of data for e-cigarette acute exposure is mainly due to the vast variety of commercially available e-cigarette device designs, pattern of use, and variability in the commercially available aerosolized solutions. (73). According to a survey querying e-cigarette users, consumers perceive the e-cigarettes as a safe and cheaper alternative to quitting smoking and helping in withdrawal symptoms during quitting of smoking (74,75).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, users can choose between various coil types (vertical, dual, triple, multiple, twisted, mesh, etc. ), made of different alloys containing iron, chromium, aluminum or nickel and coils can be wicked with several materials including organic cotton balls, silica fibers wick, or Stainless Steel Mesh among others [ 10 ]. Moreover, a wide range of resistances is available on the market with values typically ranging from 0.1 to 3 ohms allowing the vaper to modify the density and temperature of the aerosol created.…”
Section: Introductionmentioning
confidence: 99%